The roles of West African languages: development and integration - (:unkn) unknown (My University, 2020)
This volume, written in either English or French, covers a wide range of linguistic domains and West African languages. It shows the vitality and diversity of language studies in this region where the issues related to African languages, their use and place in the modern world are particularly sensitive and important.The collection brings together the developed versions of a selection of papers presented at the 30th West African Linguistic Congress (CLAO/WALC) and the 10th Annual Conference o the Linguistic Association of Ghana (LAG) held jointly in Winneba, Ghana from 31 July to 5 August 2017. The theme of this conference was the role of language in the integration and development of West Africa.
Keywords: African Research